IDENTIFIKASI KEBUTUHAN INFORMASI SEKSUAL PADA REMAJA - Sri Lestari; Suparno Suparno; Yudhi Satria Restu (Jurnal Psikologi, 2011)
Penelitian ini diinspirasi oleh peningkatan perilaku seksual dalam berpacaran dan faktasemakin mudahnya akses pornografi bagi anak. Tujuan studi adalah mengidentifikasikebutuhan akan informasi seksualitas pada remaja. Guna mendapatkan pemahaman yangkomprehensif dilakukan survei terhadap 530 remaja yang berusia 11-18 tahun, terdiri dari261 laki-laki dan 269 perempuan. Data dianalisis secara deskriptif denganmengkategorisasikan respon dari partisipan. Temuan menunjukkan bahwa remaja inginmengetahui tentang enam hal yakni perilaku seksual, hubungan seksual, makna sekssebenarnya, sistem reproduksi, dan problem seksual.AbstractThis research was inspired by the increasing of adolescent’s sexual behavior in courtship andthe fact that pornography recently more accessible to children. The purpose of this study is toidentify the needs of adolescent for sexual information. In order to gain an understanding ofthe needs of adolescents in a comprehensive manner, survey was conducted to gather data.Around 530 adolescents from 11- 18 years old participated to the survey, which consisted of261 male students and 269 female students. The data collected analyzed descriptively, bycategorizing responses from participants. The findings show that adolescents want to knowabout sexuality including six categories of topic, that are sexual behavior, intercourse, thetrue meaning of sex, reproductive system, psychosexual and sexual problem.